Congenital insensitivity to pain associated with PRDM12 mutation: Two case reports and a literature review - Yu, Hanrui; Wu, Jie; Cong, Jinju; Chen, Mingxiong; Huang, Yifei; Yu, Jifeng; Wang, Liqiang (Frontiers in Genetics, 2023)
Background:PRDM12 is a newly discovered gene responsible for congenital insensitivity to pain (CIP). Its clinical manifestations are various and not widely known. Methods: The clinical data of two infants diagnosed with CIP associated with PRDM12 mutation were collected. A literature review was performed, and the clinical characteristics of 20 cases diagnosed with a mutation of PRDM12 were summarized and analyzed. Results: Two patients had pain insensitivity, tongue and lip defects, and corneal ulcers. The genomic analysis results showed that variants of PRDM12 were detected in the two families. The case 1 patient carried heterozygous variations of c.682+1G > A and c.502C > T (p.R168C), which were inherited from her father and mother, respectively. We enrolled 22 patients diagnosed with CIP through a literature review together with our cases. There were 16 male (72.7%) and 6 female (27.3%) patients. The age of onset ranged from 6 months to 57 years. The prevalence of clinic manifestation was 14 cases with insensitivity to pain (63.6%), 19 cases with self-mutilation behaviors (86.4%), 11 cases with tongue and lip defects (50%), 5 cases with mid-facial lesions (22.7%), 6 cases with distal phalanx injury (27.3%), 11 cases of recurrent infection (50%), 3 cases (13.6%) with anhidrosis, and 5 cases (22.7%) with global developmental delay. The prevalence of ocular symptoms was 11 cases (50%) with reduced tear secretion, 6 cases (27.3%) with decreased corneal sensitivity, 7 cases (31.8%) with disappeared corneal reflexes, 5.5 cases (25%, 0.5 indicated a single eye) with corneal opacity, 5 cases (22.7%) with corneal ulceration, and 1 case (4.5%) with a corneal scar. Conclusion: The syndrome caused by PRDM12 mutation is a clinically distinct and diagnosable disease that requires joint multidisciplinary management to control the development of the disease and minimize the occurrence of complications.